PERANCANGAN DAN PEMBUATAN ANIMASI 3D TUBUH MANUSIA SEBAGAI MEDIA PEMBELAJARAN SISWA SD - Gatya Pratiniyata, MA, Sp.BMM, Gatya Pratiniyata, MA, Sp.BMM (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2022)
Learning materials of organs for elementary school children are still less attractive to students because the learning media used are less varied. This was further improvised by the author to create 3D animations to make it more interesting for students to learn. The application is made with the rigging technique, which is a technique used to move 3D objects of the human body by making an object frame so that when the skeleton is moved, the object will also move. Based on the results of data analysis from the design and manufacture of this 3D animation application, it can be used as a learning medium for elementary school children to help learn body parts in humans.